Pentacene and CuO Nanocomposite Based Self-Powered Broadband Photodetector - Srivastava A.; Singh R.; Jit S.; Tripathi S. (My University, 2025)
This work proposes an Al/Pentacene:CuO/ PEDOT:PSS/ITO structure based photodetector fabricated on an indium-tin oxide (ITO) coated glass substrate by low-cost solution method. The device uses Pentacene:CuO nanocomposite as the active layer and PEDOT:PSS as the hole transport layer (HTL). The proposed device shows a broadband photodetection properties with responsivities of 35.25 A/W, 8.74 A/W and 2.75 A/W at wavelengths of 380 nm (UV), 600 nm (visible) and 980 nm (NIR) under 1 V reverse bias voltage, respectively. The device also shows the self-biased property with the maximum responsivity of 14.4 mA/W at 600 nm under zero bias operation. The repeatability and stability of the device have been observed through repetitive device fabrication with subsequent measurements. © 1980-2012 IEEE.